A Perspective on Molecular Structure and Bonding-Breaking in Radiation Damage in Serial Femtosecond Crystallography - Carl Caleman (Crystals, 2020)
X-ray free-electron lasers (XFELs) have a unique capability for time-resolved studies of protein dynamics and conformational changes on femto- and pico-second time scales. The extreme intensity of X-ray pulses can potentially cause significant modifications to the sample structure during exposure. Successful time-resolved XFEL crystallography depends on the unambiguous interpretation of the protein dynamics of interest from the effects of radiation damage. Proteins containing relatively heavy elements, such as sulfur or metals, have a higher risk for radiation damage. In metaloenzymes, for example, the dynamics of interest usually occur at the metal centers, which are also hotspots for damage due to the higher atomic number of the elements they contain. An ongoing challenge with such local damage is to understand the residual bonding in these locally ionized systems and bond-breaking dynamics. Here, we present a perspective on radiation damage in XFEL experiments with a particular focus on the impacts for time-resolved protein crystallography. We discuss recent experimental and modelling results of bond-breaking and ion motion at disulfide bonding sites in protein crystals.